2017
DOI: 10.1212/cpj.0000000000000384
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, determinants, and effects of early seizures after thrombolysis for acute ischemic stroke

Abstract: NCT01422616.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 29 publications
3
20
0
Order By: Relevance
“…In spite of earlier evidences that seizures might be a sign of successful reperfusion (30,37), some authors suggest that patients who showed seizures after thrombolysis might present worst thrombolysis outcome when compared to patients without seizures (10,32). In this venue, our results are in line with ENCHANTED trial that showed that seizures after stroke are associated with poor outcome (73). Since studies in post-stroke epilepsy after thrombolysis are few, recent, retrospective in design, and evaluate a relatively small number of patients, their findings need further confirmation.…”
Section: Discussionsupporting
confidence: 80%
“…In spite of earlier evidences that seizures might be a sign of successful reperfusion (30,37), some authors suggest that patients who showed seizures after thrombolysis might present worst thrombolysis outcome when compared to patients without seizures (10,32). In this venue, our results are in line with ENCHANTED trial that showed that seizures after stroke are associated with poor outcome (73). Since studies in post-stroke epilepsy after thrombolysis are few, recent, retrospective in design, and evaluate a relatively small number of patients, their findings need further confirmation.…”
Section: Discussionsupporting
confidence: 80%
“…However, the fact that SaO did not independently predict poor outcome after accounting for these confounders indicates that it should be considered as a marker for an unfavorable risk profile rather than a predictor for poor outcome per se. This is in line with previous reports on early poststroke seizures being associated with unfavorable baseline risk factors, including higher stroke severity 30,32,[38][39][40][41][42] and higher admission blood glucose. 40,41 Larger, nonlacunar supratentorial infarcts with cortical involvement 31,38,39,[41][42][43] and a potential neurotoxic, epileptogenic effect of hyperglycemia 40,41 might explain these associations.…”
Section: Discussionsupporting
confidence: 93%
“…According to all these reports, early seizures indicated a poor prognosis. [30][31][32] However, SaO-patients were only a small minority, accounting for 3 out of >3,000 IVT-treated patients in the ENCHANTED (Enhanced Control of Hypertension and Thrombolysis Stroke Study) trial, 30 1 out of 12 thrombolyzed stroke patients with an early seizure, 31 and 7 out of 800 stroke patients receiving endovascular therapy. 32 Thus, putting our observations in the context of the aforementioned studies, SaO should be distinguished from early seizures, as they seem to differ with regard to prognosis after IVT-treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The ENCHANTED study identified febrile temperatures as a risk factor for acute seizures 26 , while a Norwegian register study found a relationship between NIHSS score, acute infection, and acute seizures 17 . Our study confirms several previously reported risk factors for acute symptomatic seizures such as more severe stroke and lower functional status at admission 6,16,17 .…”
Section: Discussionmentioning
confidence: 99%